Model of Community Empowerment Based on Local Wisdom through Corporate Social Responsibility in North Konawe District - Putera, Asrip; Sukotjo, Endro; Dharmawati, Tuti; Mokodompit, Eliyanti Agus (Asia Pacific Journal of Management and Education (APJME), 2020)
The purpose of this study is to develop the implementation model of CSR for nickel mining companies. This study uses interactive analysis from Milles and Huberman. The results of this study concluded that; first, to present empowerment based on local wisdom with principles: involvement of all stakeholders, ethical, village potential, sustainability. Second, intervention can be done in the form of programs; CSR program planning is carried out by stakeholders, increasing supervision, training and counseling related to CSR programs. Third, the implementation of interventions in the form of programs requires the synergy of stakeholders. This study provides solutions to mining companies and local governments to be a reference in formulating CSR programs that have a positive impact on the welfare.